2D convolution kernels of ionization chambers used for photon-beam dosimetry in magnetic fields: the advantage of small over large chamber dimensions. (29th March 2018) - Looe, Hui Khee; Delfs, Björn; Poppinga, Daniela; Harder, Dietrich; Poppe, Björn
Abstract: This study aims at developing an optimization strategy for photon-beam dosimetry in magnetic fields using ionization chambers. Similar to the familiar case in the absence of a magnetic field, detectors should be selected under the criterion that their measured 2D signal profiles M ( x, y ) approximate the absorbed dose to water profiles D ( x, y ) as closely as possible. Since the conversion of D ( x, y ) into M ( x, y ) is known as the convolution with the 'lateral dose response function' K ( x - ξ, y - η ) of the detector, the ideal detector would be characterized by a vanishing magnetic field dependence of this convolution kernel (Looe et al 2017b Phys. Med. Biol .62 5131–48). The idea of the present study is to find out, by Monte Carlo simulation of two commercial ionization chambers of different size, whether the smaller chamber dimensions would be instrumental to approach this aim. As typical examples, the lateral dose response functions in the presence and absence of a magnetic field have been Monte-Carlo modeled for the new commercial ionization chambers PTW 31021 ('Semiflex 3D', internal radius 2.4 mm) and PTW 31022 ('PinPoint 3D', internal radius 1.45 mm), which are both available with calibration factors. The Monte-Carlo model of the ionization chambers has been adjusted to account for the presence of the non-collecting part of the air volume near the guard ring. The Monte-Carlo results allow a comparison between the widths of the magnetic field dependent photon fluence response function K M ( x - ξ, y - η ) and of the lateral dose response function K ( x - ξ, y - η ) of the two chambers with the width of the dose deposition kernel K D ( x - ξ, y - η ). The simulated dose and chamber signal profiles show that in small photon fields and in the presence of a 1.5 T field the distortion of the chamber signal profile compared with the true dose profile is weakest for the smaller chamber. The dose responses of both chambers at large field size are shown to be altered by not more than 2% in magnetic fields up to 1.5 T for all three investigated chamber orientations.